Methane-derived microbial biostimulant reduces greenhouse gas emissions and improves rice yield - Kumar, Sarma Rajeev; David, Einstein Mariya; Pavithra, Gangigere Jagadish; Kumar, Gopalakrishnan Sajith; Lesharadevi, Kuppan; Akshaya, Selvaraj; Basavaraddi, Chavadi; Navyashree, Gopal; Arpitha, Panakanahalli Shivaramu; Sreedevi, Padmanabhan; Zainuddin, Khan; Firdous, Saiyyeda; et al. (Frontiers in Plant Science, 2024)
Introduction: More than half of the world's population consumes rice as their primary food. The majority of rice production is concentrated in Asia with the top 10 rice-growing countries accounting for 84% of the world's total rice cultivation. Rice production is also strongly linked to environmental changes. Among all the global sources of greenhouse gas (GHG) emissions, paddy cultivation stands out as a significant contributor to global methane (CH4) and nitrous oxide (N2O) emissions. This is expected to increase further with the projected increase of 28% in global rice output by 2050. Modifications to rice management practices are necessary, both to increase yield and mitigate GHG emissions. Methods: We investigated the effect of seedling treatment, soil and foliar application of a methane-derived microbial biostimulant on grain yield and GHG emissions from rice fields, over three seasons under 100% fertilizer conditions. Further, microbial biostimulant was also tested under 75% Nitrogen (N) levels to demonstrate its effect on grain yield. To understand the mechanism of action of microbial biostimulant on crop physiology and yield, a series of physiological, transcript and metabolite analyses were also performed. Results: Our three-season open field studies demonstrated significant enhancement of grain yield, up to 39%, with simultaneous reduction in CH4 (31─ 60%) and N2O (34─ 50%) emissions, with the use of methane-derived microbial biostimulant. Under 75% N levels, a 34% increase in grain yield was observed with microbial biostimulant application. Based on the physiological, transcript, and metabolite analyses data, we were further able to outline the potential mechanisms for the diverse synergistic effects of methane-derived microbial biostimulant on paddy, including indole-3-acetic acid production, modulation of photosynthesis, tillering and panicle development, ultimately translating to superior yield. Conclusion: The reduction in GHG emission and enhanced yield observed under both recommended and reduced N conditions demonstrated that the methane-derived biostimulant can play a unique and necessary role in the paddy ecosystem. The consistent improvements seen across different field trials established that the methane-derived microbial biostimulant could be a scalable solution to intensify rice productivity with a lower GHG footprint thus creating a win-win-win solution for farmers, customers and the environment.